2021
DOI: 10.15252/embj.2020106309
|View full text |Cite
|
Sign up to set email alerts
|

m 6 A deposition is regulated by PRMT1‐mediated arginine methylation of METTL14 in its disordered C‐terminal region

Abstract: The N6‐methyladenosine (m6A) RNA modification serves crucial functions in RNA metabolism; however, the molecular mechanisms underlying the regulation of m6A are not well understood. Here, we establish arginine methylation of METTL14, a component of the m6A methyltransferase complex, as a novel pathway that controls m6A deposition in mammalian cells. Specifically, protein arginine methyltransferase 1 (PRMT1) interacts with, and methylates the intrinsically disordered C terminus of METTL14, which promotes its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 83 publications
3
36
0
Order By: Relevance
“…Deletion of the RGG domain of METTL14 resulted in a more than 10-fold decrease in RNA binding affinity for G4-RNA1 ( K D = 419 ± 109 nM) compared to MTD3/MTD14-RGG ( Supplementary Figure S3C ). The result is in good agreement with previous reports showing that the RGG domain of METTL14 contributes remarkably to the RNA binding of METTL3/METTL14 ( 14 , 16 ). These results showed that MTD3/MTD14-RGG specifically recognizes G4-forming RNAs and the RGG domain is responsible for the strong RNA binding of METTL3/METTL14.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Deletion of the RGG domain of METTL14 resulted in a more than 10-fold decrease in RNA binding affinity for G4-RNA1 ( K D = 419 ± 109 nM) compared to MTD3/MTD14-RGG ( Supplementary Figure S3C ). The result is in good agreement with previous reports showing that the RGG domain of METTL14 contributes remarkably to the RNA binding of METTL3/METTL14 ( 14 , 16 ). These results showed that MTD3/MTD14-RGG specifically recognizes G4-forming RNAs and the RGG domain is responsible for the strong RNA binding of METTL3/METTL14.…”
Section: Resultssupporting
confidence: 93%
“…METTL14 also contains RGG repeats at the C-terminus. The RNA binding ability of METTL14 was considerably decreased in the deletion mutant of the METTL14 RGG domain, thus indicating that METTL14 RGG repeats are important for RNA binding ( 14 , 16 ). However, the RNA binding specificity of METTL14, especially toward rG4 sequences, is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It proved to be an initial signal of interaction between METTL14 and RNA polymerase II, which will afterwards implement the m 6 A modification of target mRNA. Subsequent studies have confirmed that METTL14 arginine methylation is associated with the enhanced translation of DNA repair genes (Wang Z et al, 2021). Recent studies even clarified the correlation between DNA damage repair and m 6 A-modified retrotransposable element (RTE) RNAs, in which intronic Long Interspersed Element-1 (LINE-1) interacts with the hosting gene transcription, resulting in the downregulation of its expression (Xiong et al, 2021).…”
Section: The Application Of M 6 a Modification And Its Development Prospectmentioning
confidence: 97%
“…Although METT L14 has no catalytic activity, it can form a stable complex with METTL3 to recognize the substrate RNAs [17]. In addition, the arginine methylation of METTL14 affects the binding of METTL14 to RNA substrates and the interaction with RNA polymerase II [18]. Moreover, when the ubiquitination process of METL14 is inhibited, it contributes to the stability of METL14 and its methylation of target RNA [19].…”
Section: Writersmentioning
confidence: 99%